A Chinese family with cat eye syndrome and abnormality of eye movement: First case report - Lu, Yang; Shen, Liping; Zheng, Yue; Zhang, Haichen; Liu, Yanbo; Qi, Ming; Huang, Shangzhi; Shen, Bo (Frontiers in Pediatrics, 2023)
Background Cat eye syndrome (CES) is a rare disease with a wide spectrum of phenotypic variability that is observed in 1:150,000 newborns. CES is characterized clinically by the combination of iris coloboma, anal atresia, and preauricular tags and/or pits. Many eye malformations have been reported to be associated with CES, such as iris and chorioretinal coloboma. However, an abnormality of eye movement has not been previously reported. Case presentation We report on a Chinese family carrying a 22q11.1-q11.21 duplication of 1.7Mb tetrasomy (chr22:16,500,000–18,200,000, hg38) in two generations. Based on the proband and her father’s clinical manifestations, including ophthalmological examination, cytogenetic analysis, FISH, CNV-seq, and WES, the diagnosis of CES with an abnormality of eye movement was made. Conclusion Our findings broadened the symptom spectrum of CES syndrome and laid the foundation for pathogenesis, diagnostic targets, and drug research on the abnormality of eye movement, and were helpful for early diagnosis and intervention of CES.